Sensitivitas Produksi Padi Terhadap Perubahan Iklim Di Indonesia Tahun 1974-2015 - Yanti Nurhayanti; Moko Nugroho (Agro Ekonomi, 2016)
The occurrence of climate change disrupts the productivity of paddy in Indonesia. Disruption of the paddy’s production has an impact on the availability of foodstuffs, considering paddy as staple food Indonesia society. This study aims to analyze the impact of climate change on productivity of paddy in the central acreage of paddy in period 1974-2015 by using four different climate variables. The data used are secondary data collected from Agency of Central for Statistics (BPS), Ministry of Agriculture, and National Oceanic and Atmospheric Administration (NOAA). Estimation method using data panels with Random Effect models (REM). The results showed the productivity of paddy in Indonesia are more sensitive to changes in rainfall and maximum temperature (Tmax) compared to the average temperature (Tave) and the minimum temperature (Tmin). Increased rainfall and Tmax positively impact the productivity of paddy until a specific turning point, then after that point will give the opposite impact. As for the turning point for the precipitation of 10,177 Inc./year, while Tmax on 31,35 °C. Simple simulation results demonstrate the increase in rainfall in the upper turning point of 1 % will reduce the productivity of paddy amounted 0,00796 % ceteris peribus. While the maximum temperature rise above the turning point of 1 % will reduce the productivity of paddy as much as 0,09039% ceteris peribus.